Conceptual model of the ferry que management system in ferry ports in the Republic of Croatia - Županović, Dino (Array, 2020)
This paper proposes a model for optimizing the ferry traffic and the traffic demand at the macroscopic level by using information technology (IT) and the existing tourist amenities as a key element for achieving harmonization of supply and demand, i.e. optimization of the assessed system. Proposed approach differs from the other/present models because it includes the application of the macroscopic, instead of the microscopic (local) approach, i.e. harmonization of the ferry infrastructure demand from the place of its origin (road border crossings) to the place of its operation, i.e. the ferry infrastructure, and not solely in particular segments of the ferry infrastructure.